Makna Leksikal dan Makna Kultural pada Nama Makanan dan Peralatan dalam Upacara-Upacara Adat Batak Toba: Kajian Etnolinguistik - Maya Sari Harahap; Ernanda Ernanda; Julisah Izar (Kajian Linguistik dan Sastra, 2023)
Abstract This study aims to determine the lexical and cultural meanings of food names and utensils used in Toba Batak traditional ceremonies in Simangumban District, North Tapanuli Regency. The method in this study is descriptive with a qualitative approach, while data collection techniques use observation techniques, recording techniques, interview techniques, observing techniques and note-taking techniques. While the data analysis technique uses the distribution method and the matching method. The data were obtained from informants and four types of traditional ceremonies in the Batak Toba in Simangumban District, North Tapanuli Regency became the object of his research. The results of this study are the lexical and cultural meanings of the names of the food and utensils used in the forty Toba Batak traditional ceremonies, consisting of names that use the local language. The cultural meaning obtained from the name of the food and equipment can be seen from the way it is made, how to use it, based on the ingredients and based on the characteristics of the food and equipment. The cultural meaning attached to these foods and utensils leads to hope, prayer, and the sharing of blessings. Abstrak Penelitian ini bertujuan untuk mengetahui makna leksikal dan makna kultural pada nama makanan dan peralatan yang digunakan dalam upacara-upacara adat Batak Toba di Kecamatan Simangumban, Kabaupaten Tapanuli Utara. Metode pada penelitian ini bersifat deskriptif dengan pendekatan kualitatif, adapun teknik pengumpulan data menggunakan teknik obeservasi, teknik rekam, teknik wawancara, teknik simak dan teknik catat. Sedangkan teknik analisis data menggunakan metode agih dan metode padan. Data diperoleh dari informan dan empat jenis upacara adat dalam Batak Toba di Kecamatan Simangumban, Kabupaten Tapanuli Utara menjadi objek penelitiannya. Hasil dari penelitian ini adalah makna leksikal dan makna kultural dari nama makanan dan peralatan yang digunakan dalam upacara-upacara adat Batak Toba yang berjumlah empat puluh, terdiri dari nama yang memang menggunakan bahasa daerah. Makna kultural yang diperoleh berdasarkan nama makanan dan peralatan tersebut dilihat dari cara pembuatan, cara penggunaan, berdasarkan bahan dan berdasarkan ciri dari makanan dan peralatan tersebut. Makna kultural yang terdapat pada makanan dan peralatan tersebut mengarah kepada harapan, doa dan penyampaian berkat.